From Dialogic Imagination to Polyphonic Thinking: Bakhtin in Saransk 2021 (ENTHYMEMA, 2023)
The article presents the results of the XVII International Bakhtin Conference held in Saransk (Russia) on July 5-10, 2021. The forum brought together over 100 participants from 22 countries and was held online. The 18 plenary lectures and more than 100 panels and online-discussions focused on the most important questions of the reception of Bakhtin’s heritage, and the influence of the thinker’s ideas on contemporary humanities. Presentations included works in the following areas: biography of Bakhtin, determining the place of his ideas in modern philology, philosophy and other social sciences, the theory and practice of education, and interdisciplinary research. This article analyses and contextualises the work of the conference against the background of the Bakhtin Forums of the 1980s and 2010s, which became an important part of the global Bakhtin Studies, as well as of the recent development of Bakhtin’s heritage in Russia and worldwide. The authors highlight the most important results of the last conference as supplementing and reconstructing Bakhtin’s biography, clarifying the details of the process of dialogical interaction of Bakhtin’s work with his contemporary ideas and the preceding traditions, defining the boundaries of Bakhtin’s influence on the humanities and the natural science, as well as the possibilities of integration of these disciplines under the “sign of Bakhtin”.
Keywords: Mikhail Bakhtin; Bakhtin Studies; XVII International Bakhtin Conference; Reception of academic heritage; Dialogism; Polyphony of Humanities